Fighting the cold in Ticlio Chico: Tetra Brick as heat assistant for houses - Prieto Sánchez, Roberto (2021)
Every year during winter, inhabitants of the human settlement Ciudad de Gosen (popularly known as Ticlio Chico) of Villa Maria del Triunfo district, have health problems facing a situation of poverty, essentially due to an inappropriate thermal envelope of their home. Thus, it is sought to evaluate Tetra Brik use as the main component for a new type of ceiling, due to high thermal resistance and great accessibility. Three types of Tetra Brik fixings are tested in the laboratory to know their thermal conductivity values (open boxes, closed boxes and closed boxes filled with plastic bags). Laboratory tests are carried out and calculation procedure included in the national EM.110 standard is applied to obtain the thermal transmittance values, comparing them with the values of the existing ceilings and with what it is established in the national regulation. The results show that the thermal transmittance is reduced up to 80% when compared to the existing ceiling, which is technically a great achievement because with the reuse of a container, of minimal cost and accessible to the people, houses can be kept warmer for a longer period of time.